Development and Validation of the EcoThermal Literacy Assessment: An Instrument for Environmental Literacy in Thermodynamics Learning - Rianty, Rini; Santiani, Santiani; Nasir, Muhammad (Department of Physics Education, Universitas Mataram, 2025)
Global environmental issues are becoming increasingly alarming and require serious attention. Enhancing students' environmental literacy is a strategic step in fostering awareness and sustainable actions. Thermodynamics in physics has the potential to be linked to environmental issues, but no specific assessment instrument is available to evaluate students' environmental literacy. This study aims to ensure the validity and reliability of the EcoThermal Literacy Assessment as an evaluation instrument for environmental literacy in learning thermodynamics. This instrument comprises four main dimensions: knowledge (physical and ecological systems, environmental issues, problem-solving solutions, action strategies), competence (identification, analysis, evaluation, argumentation of environmental issues), attitude (sensitivity, concern, environmental motivation), and behavior (environmental actions, problem prevention, resource management). The study employs the 4-D R&D model. Content validity is tested using Aiken’s V index, while empirical validity is examined through Pearson correlation. Reliability is measured using Cronbach’s Alpha, while discrimination power and difficulty levels are analyzed using SPSS 27. Most items exhibit high validity and good reliability (α = 0.802–0.936). The majority have moderate to good discrimination power, but some in the knowledge dimension have low discrimination power and require revision. The difficulty level is predominantly moderate to easy. This study focuses on evaluating the instrument's validity and reliability, without testing its impact on student learning outcomes. The findings can serve as a reference for assessment development and further research on the practicality of the instrument in physics learning integrated with environmental issues.